Palabras de archivo / Graciela Goldchluk y Mónica G. Pené, comp. Santa Fe: UNL, CRLA Archivos, 2013. 267 p. (Itinerarios) ISBN: 978-987-657-839-4. - Contardi, Silvia (Información, cultura y sociedad, 2014)
Reseña